All in the education of General David Petraeus - Broadwell, Paula (Penguin, 2012)
General David Petraeus is the most transformative leader the American military has seen since the generation of Marshall. In this book, military expert Paula Broadwell examines Petraeus's career, his intellectual development as a military officer, and his impact on the U.S. military. Afforded extensive access by General Petraeus, his mentors, his subordinates, and his longtime friends, Broadwell embedded with the general, his headquarters staff, and his soldiers on the front lines of fighting and at the strategic command in Afghanistan to chronicle the experiences of this American general in the terrible crucible of war. She draws on hundreds of hours of exclusive interviews with Petraeus and his top officers and soldiers to tell the inside story of this commander's development and leadership from every vantage point. Broadwell ultimately appraises Petraeus's impact on the entire U.S. military: Thanks to this man's influence, the military is better prepared to fight using a comprehensive blend of civil-military activities.--From publisher description.